Challenges To Pharmacy Students Training in Community Pharmacies - Mohamed Azmi Hassali; Mahmoud Sa'di Mohammad Al-Haddad (Archives of Global Professionals, 2010)
Pharmacy students are the future health care practitioners who will provide not only quality pharmaceutical services but also health promotion guidance to communities. If they are not well trained in the community health needs,this will directly affect on the future quality of care in the community. Worldwide pharmacy graduates are found more inclined to practice in community pharmacy setting. This initiative will not only help them in practicing their knowledge but also act as a profitable earning source.